2000
DOI: 10.1046/j.1365-2222.2000.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal hyperosmolar challenge with a dry powder of mannitol in patients with allergic rhinitis. Evidence for epithelial cell involvement

Abstract: Epithelial cell seems to be involved with the mediator response to airway hyperosmolar challenge. The roles of sensory c-fibre nerve cell and mast cell remained less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
(54 reference statements)
2
23
0
Order By: Relevance
“…2). Hyperosmolar challenge initiates the release of 15S-HETE in nasal lavage fl uid [29] and in nasal polyp cells in vitro. We found that relative to nonasthmatics, the level of 15S-HETE in the airways is increased after exercise challenge in asthmatics with EIB [30••].…”
Section: Role Of Leukotrienes In the Pathophysiology Of Eibmentioning
confidence: 99%
“…2). Hyperosmolar challenge initiates the release of 15S-HETE in nasal lavage fl uid [29] and in nasal polyp cells in vitro. We found that relative to nonasthmatics, the level of 15S-HETE in the airways is increased after exercise challenge in asthmatics with EIB [30••].…”
Section: Role Of Leukotrienes In the Pathophysiology Of Eibmentioning
confidence: 99%
“…Nasal insufflation with chemokines, such as IL-8, 26 eotaxin, 27 and regulated on activation normally T-cell expressed and secreted (RANTES), 28 has also been used to evaluate the effect and time course of their effect on cell recruitment into the nasal lumen. Studies have also been undertaken to investigate the effects of non-IgE-related stimuli, such as hyperosmolar challenge, aspirin, and sodium metabisulfite, on mediator release within the nose, [29][30][31][32] and with or without therapeutic intervention, to gain insight into the magnitude of effect and mechanism of action of differing pharmacologic modalities on cell recruitment, cell activation, and induced vascular permeability. [33][34][35][36][37][38][39][40][41] Although these approaches have been widely used in the limited research setting, they have been less widely applied as a means of objectively monitoring nasal disease in the clinical trial setting.…”
Section: Nasal Lavagementioning
confidence: 99%
“…It may be argued that the hyperosmotic medium itself could cause ␣ 2 M release. However, this seems unlikely since hyperosmotic mannitol failed to cause significant release of ␣ 2 M from human epithelial cells (49). In addition to liver cells and astroglia, blood cells may also produce ␣ 2 M (50).…”
Section: Fig 2 Radial Immunodiffusion Analysis Demonstrating Increamentioning
confidence: 99%